Changes in choice reaction time during and after 8 days exhaustive cycling are not related to changes in physical performance - ten Haaf, T.; van Staveren, S.; Iannetta, D.; Roelands, B.; Meeusen, R.; Piacentini, M. F.; Foster, C.; Koenderman, L.; Daanen, H. A. M.; de Koning, J. J. (International Journal of Sports Physiology and Performance, 2018)
Purpose: Reaction time has been proposed as a training monitoring tool, but to date, results are equivocal. Therefore, it was investigated whether reaction time can be used as a monitoring tool to establish overreaching. Methods: The study included 30 subjects (11 females and 19 males, age: 40.8 [10.8] years, VO2max: 51.8 [6.3] mL/kg/min) who participated in an 8-day cycling event. The external exercise load increased approximately 900% compared with the preparation period. Performance was measured before and after the event using a maximal incremental cycling test. Subjects with decreased performance after the event were classified as functionally overreached (FOR) and others as acutely fatigued (AF). A choice reaction time test was performed 2 weeks before (pre), 1 week after (post), and 5 weeks after (follow-up), as well as at the start and end of the event. Results: A total of 14 subjects were classified as AF and 14 as FOR (2 subjects were excluded). During the event, reaction time at the end was 68 ms (95% confidence interval, 46-89) faster than at the start. Reaction time post event was 41 ms (95% confidence interval, 12-71) faster than pre event and follow-up was 55 ms faster (95% confidence interval, 26-83). The time by class interaction was not significant during (P=.26) and after (P=.43) the event. Correlations between physical performance and reaction time were not significant (all Ps>.30). Conclusions: No differences in choice reaction time between AF and FOR subjects were observed. It is suggested that choice reaction time is not valid for early detection of overreaching in the field.